Letter - Westbury & District Trades and Labour Council, 9 May 1926 (Westbury)
1926-05-09 "Letter - Westbury & District Trades and Labour Council, 9 May 1926" [g0346001.jpg], 9 May 1926, Westbury & District Trades and Labour Council Local Organisation